Being an older family caregiver does not impact healthcare and mortality: Data from the study 'Good Aging in Skåne'. Issue 2 (March 2022) - Elmståhl, Sölve; Lundholm-Auoja, Nathalie; Ekström, Henrik; Sandin Wranker, Lena
Background: Will being a caregiver further impact the health of a group already at risk of adverse health due to old age? This study aimed to answer the questions whether short- and long-term healthcare consumption and mortality differ between informal caregivers and non-caregivers and between high-burden and low-burden informal caregivers. Method: The study population consisted of 423 caregivers and 3444 controls from the Swedish national general population study 'Good Aging in Skåne'. Caregivers were divided into those reporting high and low caregiver burden and information on caregiver status was collected from questionnaires. Data for mortality and healthcare consumption (inpatient and outpatient visits) were obtained from The National Board of Health and Welfare. Mortality was tested with Cox regression models and healthcare consumption with logistic regression models, adjusted for sociodemographic covariates, Activities of daily living (ADL) and number of chronic diseases. Results: Caregivers were younger than non-caregivers, had higher educational background, more independent in ADL and more often men. Of 423 caregivers, 73 (17.3%) reported experiencing high caregiver burden. High-burden caregivers were older, more dependent in personal ADL and gave more hours of care than those reporting low burden. In adjusted regression models, we found no differences in either consumption of healthcare nor mortality between caregivers and non-caregivers and high-burden v. low-burden caregivers looking at short-term (1 and 3 years) and long-term (10 and 15 years) follow-up periods. Conclusions: Our findings suggest that the characteristic of being a family caregiver does not have an impact on mortality or physical health measured as inpatient admissions or instances of primary care.